2011
DOI: 10.4238/2011.december.14.6
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Influence of Arg72Pro polymorphisms of TP53 on the response of buccal cells to radiotherapy

Abstract: Polymorphisms in the TP53 gene codon 72 (Arg72Pro) influence apoptosis induction and DNA damage repair. We evaluated how variants of protein p53 (p53Arg and p53Pro) affect cell death and DNA damage repair by analyzing the frequencies of karyorrhexis and micronuclei. There were significant differences in the frequency of karyorrhexis between the three p53 genotypes (Arg/Arg, Arg/Pro, and Pro/Pro), between samples taken before and after radiotherapy, and between patients and controls. The frequency of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A study by Schwartz et al in 2011 using the human lymphoblast cells revealed that cell lines with homozygous Proline coding allele were more likely to be resistant to radiation-induced chromatid break formation in G 2 chromosomal radiosensitivity assay compared to those containing two arginine coding alleles [36]. Another study by Pereira et al in 2011 revealed that the homozygous arginine coding alleles increase the number of cells with karyorrhexis in buccal cells of head and neck cancer patients after the first session of radiotherapy [37]. The effect of low dose and low dose rate of radiation is inconsistent and inconclusive [38].…”
Section: Association Between Tp53 Arg72pro Polymorphism and Radiosensmentioning
confidence: 99%
“…A study by Schwartz et al in 2011 using the human lymphoblast cells revealed that cell lines with homozygous Proline coding allele were more likely to be resistant to radiation-induced chromatid break formation in G 2 chromosomal radiosensitivity assay compared to those containing two arginine coding alleles [36]. Another study by Pereira et al in 2011 revealed that the homozygous arginine coding alleles increase the number of cells with karyorrhexis in buccal cells of head and neck cancer patients after the first session of radiotherapy [37]. The effect of low dose and low dose rate of radiation is inconsistent and inconclusive [38].…”
Section: Association Between Tp53 Arg72pro Polymorphism and Radiosensmentioning
confidence: 99%
“…Druzhinin et al (2015) reported that the frequencies of chromosomal aberrations in peripheral blood lymphocytes were significantly elevated in longterm resident children in a boarding school under con ditions of high exposure to radon. The polymorphism TP53 Arg72Pro (rs1042522) can affect the induction of cell apopto sis (Pereira et al, 2011) and the repair of damaged DNA (Hu et al, 2005). It is possible that the Arg72Pro genotype does not promote efficient DNA repair or apoptosis in comparison with Arg72Arg and these events lead to malignant transformation of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the p53 Pro72P subtype is more easily located in the nucleus, while the p53 Arg72R subtype is more easily located in the mitochondria under stress (22). Therefore, it is possible that the p53 Pro72p subtype may more effectively induce gene expression of nuclear DNA compared with the p53 Arg72R subtype (23). The polymorphism of the 72 codon of the p53 gene can affect the induction of cell apoptosis and the repair of damaged DNA, which are functions closely associated with the maintenance of the integrity of the nuclear envelope (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that the p53 Pro72p subtype may more effectively induce gene expression of nuclear DNA compared with the p53 Arg72R subtype (23). The polymorphism of the 72 codon of the p53 gene can affect the induction of cell apoptosis and the repair of damaged DNA, which are functions closely associated with the maintenance of the integrity of the nuclear envelope (23,24). In addition, the polymorphism of the 72 codon of the p53 gene may affect the accumulation of mitochondrial DNA mutations by combining with DNA polymerase γ (19).…”
Section: Discussionmentioning
confidence: 99%